What makes people anxious about life after the age of 65? Evidence from international survey research in Japan, the United States, and China - Yoshihiko Kadoya (Osaka University, Institute of Social and Economic Research (ISER), 2012)
In order to respond to the social security needs of an increasingly aged population, many governments with limited budgets are required to focus available resources on the direct causes of people's anxieties about aging. This study investigated the causes of people's anxieties about life after the age of 65 using household data from countries with different social contexts: Japan, the United States, and China. This research uncovered three major findings. First, the speed of population aging does not always make people anxious about life at an older age. Second, high financial status effectively lessens people's levels of anxiety about their older years in Japan and the United States. Third, living with a child does not necessarily lessen people's concern about life after 65.
Keywords: H53; I38; 330; ageing; social security; future concern; precautionary saving; comparative studies; Alternde Bevölkerung; Sparen; Meinung; Altersvorsorge; Alte Menschen; Vergleich; Japan; USA; China